Never - Follett, Ken (Viking, 2021)
Navigating terrorist attacks, illegal arms trading and smear campaigns, Pauline Green, the country's first women president, is caught in a complex web of alliances with the most powerful counties that are being orchestrated by the enemy, and only those with the most elite skills can stop the inevitable.